Interactions between Candida albicans and the resident microbiota - Li, Hao; Miao, Ming-xing; Jia, Cheng-lin; Cao, Yong-bing; Yan, Tian-hua; Jiang, Yuan-ying; Yang, Feng (Frontiers in Microbiology, 2022)
Candida albicans is a prevalent, opportunistic human fungal pathogen. It usually dwells in the human body as a commensal, however, once in its pathogenic state, it causes diseases ranging from debilitating superficial to life-threatening systemic infections. The switch from harmless colonizer to virulent pathogen is, in most cases, due to perturbation of the fungus-host-microbiota interplay. In this review, we focused on the interactions between C. albicans and the host microbiota in the mouth, gut, blood, and vagina. We also highlighted important future research directions. We expect that the evaluation of these interplays will help better our understanding of the etiology of fungal infections and shed new light on the therapeutic approaches.